Low complexity visual UAV track navigation using long‐wavelength infrared. Issue 6 (11th January 2021) - Rosser, Kent; Nguyen, Tran Xuan Bach; Moss, Philip; Chahl, Javaan
Abstract: Visual navigation is a commonly researched alternative to the use of global navigation satellite systems in challenging environments where satellite signals are not available. However, the vast majority of visual navigation techniques studied to date require scene illumination of some form. In this study, we use a low‐resolution long‐wave infrared (LWIR) image sensor sensitive to thermal emissivity within an optical flow processing engine to extend a low complexity track‐based navigation scheme for fixed wing aircraft to operate at night. A mixture of closed and open loop flight experiments conducted on a small UAV integrated with the new sensor demonstrate: accurate track‐based navigation in visual darkness; that the LWIR sensor performs equivalently to the benchmark optical flow sensor during daylight and continues to operate in low light; and that the LWIR sensor is able to detect suitable textures for operation at night across a wide span of altitudes. These results demonstrate utility of optical flow algorithms with low‐resolution thermal scenes as a novel aircraft navigation sensor for day and night operation.